Building localized interactions between universities and cities through university spatial development - Benneworth, Paul; Charles, David; Madanipour, Ali (Taylor and Francis, 2010)
Universities are important players in the global development of knowledge economy, alongside being significant contributors to the economic development of their host cities. They are both significant knowledge enterprises and the suppliers of the human and intellectual capital on which the knowledge based economy depends. What seems under-explored is how deliberative partnerships between universities and city authorities can develop around projects of mutual benefit, especially based on campus development. In this paper with the help of five case studies (QUT, MIT, Harvard, Twente and Newcastle universities), we investigate how the spatial development of universities can be one of the main meeting points between the city and university and how it can be used for stimulating economic development and managing growth. These cases show that university-city collaborative initiatives focussed on the university properties represent a desire to produce creative and competitive new urban spaces, which reinforce the position of the university and the city in global economy. They also show that these developments need to be jointly managed to avoid undesirable impacts on either side.